Strategi Komunikasi Personal Branding Nusibah Jazuli dalam Pembentukan Citra Positif Partai Politik - Farhatuz Zahra; Agnia Mumtaza; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research aims to identify the personal branding strategy implemented by Nusaibah Jazuli, a PKS faction member of the South Tangerang City Regional People's Representative Council (DPRD), in building a positive image during the 2024 Election campaign. The advancement of social media has transformed how politicians build and manage their self-image, making a strong personal brand a crucial tool for young politicians to achieve credibility and differentiation amid fierce competition. Employing a qualitative descriptive method, the study analyzes Nusaibah's approach using the Personal Branding Pyramid framework (determine who you are, determine what you do, position yourself, and manage your brand). The findings indicate that this strategy successfully built her reputation and credibility. This success is underpinned by the